رؤیت ہلال میں معاصر فلکیاتی حسابات سے استفادے کا شرعی جائزہ: Shariah Analysis of modern astronomical calculations for moon sighting - Dr Noor Wali Shah; Dr. Nisar Akhtar; Dr. Saeed Ahmad (Al Manhal Research Journal, 2022)
Moon sighting has great importance in Islam. Fasting in the month of Ramadhan, Celebrating Eid Ul Fitr, Eid ul Adha, performing hajj and paying Zakat etc. all are related with Islamic lunar calendar. The lunar calendar is based on the rotation of moon and with the help of modern astronomical calculation it is very easy to know about the exact location of the moon. That’s way it is very easy to design a lunar calendar for upcoming years and centuries and no one can find any contradiction in that. If we study hadith we find that The Prophet SAW has ordered his companions to fast if the moon of Ramadhan is viewed by naked eyes and to celebrate The Eid ul Fitr if it is viewed by naked eyes. Here a question arises that is it allowed to get assistance from modern astronomical calculations and based on that to announce the start of an Islamic month. The answer is yes, In this paper we have evaluated the scientific side of moon sighting in the light of Islam, whether getting assistance from scientific and astronomic laws and calculations in moon sighting is allowed in Islam or not and have concluded that although depending on these astronomic laws is not permitted but getting help from them while sighting moon with naked eyes is allowed and appreciated.